Brazilian apartheid: racism and segregation in Salvador, Brazil - Rotondano, Ricardo Oliveira (International journal of sociology and social policy, 2019)
Purpose The purpose of this paper is to analyse empirically the racial relations of segregation of the black population in the city of Salvador, Brazil, which built according to a subtle model of the construction of differentiated spaces for the white population and the black population in the city. Design/methodology/approach The methodology used for the construction of this manuscript was that of the action research, through the insertion of the researcher within the field of study, obtaining observational perceptions of the inhabited place and collecting reports of the research subjects inserted in the field of study. Findings The present research obtained as final results the explicit characterisation of a veiled and subtle model of racial segregation imposed on the black population of the city of Salvador, manifesting the clear prejudice of the white population and also a state racism directed to the oppressed black population. Originality/value The originality of the research consists in the fact that there is no research modality within Brazil for the analysis of historical apartheid policies. The Brazilian state, in this sense, appears within the current framework of academic research as a clear incentive and propagator of governmental actions that corroborate the maintenance of the exclusionary city system, which separates the black and white population in differentiated social spaces.